Efficient Synthesis of RuO2 Nanoparticle with excellent activity for one‐pot Synthesis of 2, 3‐disubstituted quinazolin‐4(1H)‐ones. Issue 5 (25th October 2019) - Raghu, M. S.; Prasad, K. N. N.; Jayanna, B. K.; Kumar, C. B. Pradeep; Kumar, K. Yogesh; Prashanth, M. K.
Abstract: An efficient one‐pot synthesis of 2, 3‐disubstituted quinazolin‐4(1H)‐ones has been developed via ruthenium oxide (RuO2 ) nanoparticle catalyzed cyclocondensation method. Various 2, 3‐disubstituted quinazolin‐4(1H)‐ones have been synthesized from N ‐(4‐methoxyphenyl)‐2‐(methylamino)benzamide with aromatic substituted aldehydes with excellent yields. Ruthenium oxide nanoparticle has been generated in situ from the reaction of ruthenium chloride. The synthesized nanoparticle is well characterized by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and powder X‐ray Diffraction (XRD) methods. The present protocol offers the advantages of mild reaction conditions, base free, short reaction time, excellent yields, reusable and easy workup.